STRATEGI BUDAYA UNTUK PEMULIHAN USAHA KECIL DAN MENENGAH (UKM) DI YOGYAKARTA PASCAGEMPA - Erwan Agus Purwanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
In May 2U, 2006 earthquake hit Yogyakarta and Central Java measured 5.9 on the Richter scale and lasted for S2 seconds. The impact of the earthquake in May 2U, 2006 which hit Yogyakarta and Central Java was very devastating. To add the anguish, one of the most important economic pillars of Yogyakarta's inhabitants: the Small and Medium Enterprises (SMEs) were also severely affected by the calamity. The preliminary assessment done by various institutions found that thousands SMEs actors have lost their enterprises. Moreover, ten thousands SMEs workers lost their jobs by which they make a living. To easy the pain of the impact of this tragedy, this paper offers a scenario to utilize the strong altruism culture of Yogyakarta's community as an economic instrument to help the SMEs actors to rebuild their business. The cultural instrument here means that people in Yogyakarta are suggested to use their moral judgment rather than rational one when making a choice to fulfill their daily needs: that is by switching their preference from buying branded manufactured goods made by big factories to simpler products made by SMEs. This community movement, hopefully, will boost the demand of SMEs products which in the end could support the efforts of the SMEs actors to recover their business.